FAKTOR-FAKTOR YANG MEMPENGARUHI KINERJA PEGAWAI DIKANTOR PENDIDIKAN KABUPATEN CIREBON - Hengki Hardiansah; Vina Andita Pratiwi (PT. Berkah Digital Teknologi, 2023)
Purpose: The purpose of this study was to determine the factors of influence employee performance in the Cirebon District Education Office. Research Methodology: This research uses accidental sampling method with a sample of 37 employees. Data collection is done by filling out the questionnaire for the ability factor and motivation factor with employee performance. Results: Furthermore, the data collected was analyzed using SPSS 26.0 for Windows with a significance level (α) of 0.05. The results showed there was an influence of the ability to see the tcount value of the ability factor variable (X1) of 4,311 ≥t_table (0.68137) and motivational actors with the t_count value of the variable (X2) of 4,871 ≥ t table (0.68137). And based on the value of β and t_calculate it can be seen that the variable that has a dominant influence on employee performance is the ability factor variable with a value of β (0.701) and tcount (4,871) which is greater than the other variables and also the significance value of t_calculate the best results. And from the results of the study it is expected that employees at the Department of Education, can provide much better performance even the people who come. Limitations: Small Sample Size: The study used a relatively small sample size of 37 employees, which may limit the generalizability of the findings to a larger population. The results may not accurately represent the entire workforce at the Cirebon Regency Education Office or other similar educational institutions. Accidental Sampling: The research employed an accidental sampling method, which may introduce bias and affect the representativeness of the sample. The findings may not reflect the views and experiences of the entire employee population, as those who were not included in the sample might have different perspectives. Reliance on Self-Reported Data: The study collected data through self-reported questionnaires, which may be subject to response biases such as social desirability or recall bias. The accuracy and reliability of the results depend on the participants' honesty and ability to accurately recall and report their abilities and motivations. Single-Location Study: The research focused solely on the Cirebon Regency Education Office in a specific geographical area. The findings may not be applicable to other educational offices or institutions located in different regions or cultural contexts. Contribution: Organizational Improvement: The Findings Can Provide Valuable Insights For The Cirebon Regency Education Office In Identifying The Factors That Influence Employee Performance. By Understanding The Significance Of Ability And Motivation Factors, The Office Can Develop Targeted Strategies To Enhance Employee Performance And Productivity. Human Resource Management: The Study Contributes To The Field Of Human Resource Management By Highlighting The Importance Of Factors Such As Ability And Motivation In Employee Performance. It Emphasizes The Need For Organizations To Focus On Developing Employees' Skills And Providing A Motivating Work Environment To Foster Higher Performance Levels. Educational Management: The Research Findings Can Benefit Educational Management In The Cirebon Regency And Similar Areas By Emphasizing The Key Factors That Influence Employee Performance Within Educational Organizations. This Knowledge Can Inform Decision-Making Processes And Help Enhance The Overall Quality Of Education Delivery In The Region. Further Research: The Study Can Serve As A Foundation For Future Research On Employee Performance In Educational Institutions. Researchers Can Build Upon The Findings And Expand The Investigation To Include Larger Sample Sizes, Different Locations, And Additional Variables To Gain A More Comprehensive Understanding Of The Factors Influencing Employee Performance In The Education Sector.